2019
DOI: 10.3390/s19153414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AlN and BCN Thin Film Multilayer Design on the Reaction Time of Ni/Ni-20Cr Thin Film Thermocouples on Thermally Sprayed Al2O3

Abstract: Thin film thermocouples are widely used for local temperature determinations of surfaces. However, depending on the environment in which they are used, thin film thermocouples need to be covered by a wear or oxidation resistant top layer. With regard to the utilization in wide-slit nozzles for plastic extrusion, Ni/Ni-20Cr thin film thermocouples were manufactured using direct-current (DC) magnetron sputtering combined with Aluminiumnitride (AlN) and Boron-Carbonitride (BCN) thin films. On the one hand, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Many authors have reported the development of Ni-20Cr coatings on steel alloys [17][18][19][20][21][22][23], but no researcher has deposited nano yttria-stabilized zirconia (Y2O3/ZrO2) (YSZ) reinforced composite coatings on boiler steels. Therefore, there is a scope to develop new nano yttria-stabilized zirconia (YSZ) reinforced (Ni-20Cr) nanocomposite coatings and subsequently deposit and investigate the microstructure, porosity, and microhardness of these newly developed composite coatings on boiler tube steel.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported the development of Ni-20Cr coatings on steel alloys [17][18][19][20][21][22][23], but no researcher has deposited nano yttria-stabilized zirconia (Y2O3/ZrO2) (YSZ) reinforced composite coatings on boiler steels. Therefore, there is a scope to develop new nano yttria-stabilized zirconia (YSZ) reinforced (Ni-20Cr) nanocomposite coatings and subsequently deposit and investigate the microstructure, porosity, and microhardness of these newly developed composite coatings on boiler tube steel.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the development of technology intelligence, integration, and miniaturization, thin-film thermocouples based on Micro-Nano manufacturing technology are gradually taking the dominant position with the advantages of small size, lightweight, low power consumption, high reliability, high sensitivity, easy integration, and resistance to the harsh working environment [16][17][18][19]. In 2011, Varrenti demonstrated a 50 nm thick chromium-nickel thin-film thermocouple on a semiconductor substrate with a thin-film thermocouple with a Seebeck coefficient calibrated to 10.37 µV/ • C. The measurable temperature range is 20 • C to 160 • C. The thermal accuracy of the integrated system can be less than 1 • C and shows good repeatability of the Seebeck coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate measurement of the surface temperature of a turbine blade and the control of its temperature distribution is an important basis for diagnosing turbine blade failure. The methods of measuring the surface temperature of turbine blades mainly include thin-film thermocouples [ 21 , 22 , 23 ], temperature indicating paint [ 24 ], infrared radiation [ 25 , 26 , 27 ], and irradiation crystals [ 28 , 29 , 30 ]. Based on the advantages of irradiating crystals, the authors [ 20 ] proposed an easy and cheap method of temperature measurement using a thin-film crystal.…”
Section: Introductionmentioning
confidence: 99%